Toward 1.8 Tb/s CAP Schemes for Short Reach Optical Communication Systems - Majeed, Majidah H.; Fyath, Raad Sami (Discoveries in Agriculture and Food Sciences, 2017)
Wavelength-division multiplexed (WDM)carrierless amplitude/phase (CAP) modulation is proposed for1.8 Tb/sfor short reach optical communication system. The system uses 16 channels, each operates at 112 Gb/s. A single-band (SB) CAP and multiband (MB) CAP are adopted for each channel as advanced modulation format with high spectral efficiency. The system performance at C and O operating bandsare investigated withchannel spacing of 100 GHz.The system is simulated using OptiSystem14.0 software package and the results reveal that the maximum allowable distance at BER of is 3.45km and 2.11 km for SB-CAP and MB-CAP operating at C-band with 0 dB laser power, respectively. These values to be compared with 4.5 km and 1.8 km, respectively, for O-band operation.